Vasoconstriction Response to Mental Stress in Sickle Cell Disease: The Role of the Cardiac and Vascular Baroreflexes - Thuptimdang, Wanwara; Shah, Payal; Khaleel, Maha; Sunwoo, John; Veluswamy, Saranya; Kato, Roberta M.; Coates, Thomas D.; Khoo, Michael C. K. (Frontiers in Physiology, 2021)
Recent studies have shown that individuals with sickle cell disease (SCD) exhibit greater vasoconstriction responses to physical autonomic stressors, such as heat pain and cold pain than normal individuals, but this is not the case for mental stress. We sought to determine whether this anomalous finding for mental stress is related to inter-group differences in baseline cardiac and vascular autonomic function. Fifteen subjects with SCD and 15 healthy volunteers participated in 3 mental stress tasks: N-back, Stroop, and pain anticipation. R-R interval, arterial blood pressure and finger photoplethysmogram (PPG) were continuously monitored before and during these mental stress tasks. The magnitude of vasoconstriction was quantified using change in PPG amplitude from the baseline period. To represent basal autonomic function, we assessed both cardiac and vascular arms of the baroreflex during the baseline period. Cardiac baroreflex sensitivity (BRSc) was estimated by applying both the “sequence” and “spectral” techniques to beat-to-beat measurements of systolic blood pressure and R-R intervals. The vascular baroreflex sensitivity (BRSv) was quantified using the same approaches, modified for application to beat-to-beat diastolic blood pressure and PPG amplitude (PPGa) measurements. Baseline BRSc was not different between SCD and non-SCD subjects, was not correlated with BRSv, and was not associated with the vasoconstriction responses to mental stress tasks. BRSv in both groups was correlated with mean PPGa, and since both baseline PPGa and BRSv were lower in SCD, these results suggested that the SCD subjects were in a basal state of higher sympathetically-mediated vascular tone. In both groups, baseline BRSv was positively correlated with the vasoconstriction responses to N-back, Stroop and pain anticipation. After adjusting for differences in BRSv within and between groups, we found no difference in the vasoconstriction responses to all 3 mental tasks between SCD and non-SCD subjects. The implications of these findings are significant in subjects with SCD since vasoconstriction reduces microvascular flow and prolongs capillary transit time, increasing the likelihood for VOC to be triggered by exposure to stressful events.